2022
DOI: 10.5334/ijic.6028
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Optimal Care Pathways for Aboriginal and Torres Strait Islander People With Cancer: A Survey of Rural Health Professionals’ Self-Rated Learning Needs

Abstract: In 2018, the Optimal Care Pathway (OCP) for Aboriginal and Torres Strait Islander people with cancer was developed in Australia to improve the cancer care experiences and outcomes of Aboriginal and Torres Strait Islander people. Methods:Our study examined health professionals' learning needs to meet the clinical practice requirements of the new OCP. An electronic questionnaire was distributed to 120 health professionals providing oncology care in two rural areas in Victoria, Australia. Questions included demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The importance of the familiarity and continuity of primary care, and strong therapeutic relationships was also noted in the review by Meiklejohn et al (2017) of perspectives of Aboriginal and Torres Strait Islander cancer survivors. A survey of Victorian health professionals conducted by Ristevski et al (2022) also confirmed that Aboriginal primary health services were appropriate locations for support outside of hospital. Systems barriers were most apparent around the delay in access to colonoscopy and financial access to surgical services.…”
Section: Discussionmentioning
confidence: 93%
“…The importance of the familiarity and continuity of primary care, and strong therapeutic relationships was also noted in the review by Meiklejohn et al (2017) of perspectives of Aboriginal and Torres Strait Islander cancer survivors. A survey of Victorian health professionals conducted by Ristevski et al (2022) also confirmed that Aboriginal primary health services were appropriate locations for support outside of hospital. Systems barriers were most apparent around the delay in access to colonoscopy and financial access to surgical services.…”
Section: Discussionmentioning
confidence: 93%
“…Delivering cultural safety training to hospitals or community services staff could be essential to improving the cultural safety of Indigenous people with cancer. A recent study found that around half of the healthcare professionals had attended cultural safety training to treat Indigenous people to better implement the optimal care of cancer pathways in primary healthcare [ 15 ]. Even a single workshop improved healthcare professionals’ confidence concerning cultural differences [ 46 ] and may improve healthcare professionals’ understanding of maintaining the privacy of cancer care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research focusing on healthcare professionals has also highlighted barriers to cancer outcomes for Indigenous peoples, including interactions between patients and healthcare professionals [ 5 , 6 ] and cultural sensitivity among healthcare providers [ 15 ]. A study of Indigenous cancer care providers highlighted essential cancer care components: culturally competent and responsive care; providing psychological support; ascertaining and responding to patient needs; delivery of practical assistance; and advocating for Indigenous health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%